Pengaruh Neraca Transaksi Berjalan Terhadap Pertumbuhan Ekonomi Indonesia - Sudirman Sudirman (Journal Development, 2014)
Indonesia is a country with an open economy, which means activities in developing economies are heavily influenced by the foreign sector. The openness of the economy has an impact on a country's balance of payments relating to the flow of trade and capital flows. Various efforts are needed to increase exports in order to increase the Reserves . While the policy on imports directed to protect and develop domestic production. On the other hand domestic funding constraints need to be addressed to maintain fluency in development, so that funds from abroad in the form of loans or assistance that is still very necessary. All of this is intended to maintain the stability of International Balance of Payments (BOP) that prose foreign trade can be sustained. In one there is a structure of balance of payments current account (current account). In theory consists of the balance of current account balance on goods, services account, and unilateral transfers. Positive value or an increase in the current account means there is a current account surplus and vice versa if it is negative or the so-called current account deficit decline.